2022
DOI: 10.3389/fsurg.2022.863273
|View full text |Cite
|
Sign up to set email alerts
|

Complete Video-Assisted Thoracoscopic Surgery and Traditional Open Surgery for Elderly Patients With NSCLC

Abstract: Objective:To observe the efficacy of complete video-assisted thoracoscopic surgery (CVATS) and traditional open surgery (TOS) in the treatment of elderly patients with non-small cell lung cancer (NSCLC) and their influence on cardiopulmonary function.MethodsA total of 120 elderly patients with primary NSCLC who were treated surgically in our hospital from January 2018 to January 2021 were selected and divided into the study group and the control group according to the different surgical procedures, 60 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Patients who underwent RATS were associated with the shortest operation duration (RATS 100.85 ± 29.06 vs VATS 113.75 ± 33.40 vs OL 112.76 ± 22.85 mins, p <0.001) and the least blood loss (p <0.001). RATS also led to the shortest ICU stay (RATS 0[0-1] vs VATS 1[0-1] vs OL 1[0-1] days, p = 0.004), chest tube drainage duration (RATS 4 [3][4][5][6] vs VATS 5 [4][5][6] vs OL 5 [5][6][7] days, p <0.001) and postoperative stay (RATS 5 [4][5][6] vs VATS 5 [4][5][6][7] vs OL 6 [5][6][7][8] days, p <0.001) among three surgical approaches, and had a similar conversion rate compared with VATS (p = 0.184). However, the overall cost in the RATS group was $14838.26 ± 2841.65, which was significantly higher than that in the VATS ($13190.51 ± 2120.18, p <0.001) and OL ($13429.58 ± 2582.36, p <0.001) group.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who underwent RATS were associated with the shortest operation duration (RATS 100.85 ± 29.06 vs VATS 113.75 ± 33.40 vs OL 112.76 ± 22.85 mins, p <0.001) and the least blood loss (p <0.001). RATS also led to the shortest ICU stay (RATS 0[0-1] vs VATS 1[0-1] vs OL 1[0-1] days, p = 0.004), chest tube drainage duration (RATS 4 [3][4][5][6] vs VATS 5 [4][5][6] vs OL 5 [5][6][7] days, p <0.001) and postoperative stay (RATS 5 [4][5][6] vs VATS 5 [4][5][6][7] vs OL 6 [5][6][7][8] days, p <0.001) among three surgical approaches, and had a similar conversion rate compared with VATS (p = 0.184). However, the overall cost in the RATS group was $14838.26 ± 2841.65, which was significantly higher than that in the VATS ($13190.51 ± 2120.18, p <0.001) and OL ($13429.58 ± 2582.36, p <0.001) group.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…Thus, minimally invasive surgeries (MISs) which could reduce postoperative complications and shorten postoperative hospital stay, such as video-assisted thoracoscopic surgery (VATS), have been widely adopted (7). Numerous studies have suggested that VATS achieved better perioperative outcomes and similar longterm survival compared to OL for older NSCLC patients (8)(9)(10). Nowadays, robotic-assisted thoracoscopic surgery (RATS), an innovative MIS with high-quality visualization and great maneuverability which allows surgeons to perform complex operations with great convenience and precision, has been increasingly applied in treating NSCLC (11).…”
Section: Introductionmentioning
confidence: 99%
“…Obwohl mittels Thorakotomie eine Resektion an der Lunge meist schneller erfolgen kann als mittels videoassistierter Thorakoskopie, zeigen aktuelle Studien [65] Mit diesem Ansatz wurden im Alter inzwischen nebst Pleuraergüssen, Pleurabiopsien und Empyeme [67] in einem Einzelzentrum 36 Lobektomien bei 65-bis 87-Jährigen mit NSCLC im Stadium I und II durchgeführt [68]. Dasselbe Zentrum hat in einer aktuellen Propensity-Matched-Studie ihre nichtintubierten Thorakoskopien (n = 79) mit ihren herkömmlichen Thorakoskopien (n = 158) bei gut selektionierten ≥ 75jährigen PatientInnen verglichen [69].…”
Section: Operationszugangunclassified
“…Obwohl mittels Thorakotomie eine Resektion an der Lunge meist schneller erfolgen kann als mittels videoassistierter Thorakoskopie, zeigen aktuelle Studien [ 65 ] für Letztere auch bei älteren PatientInnen eine deutliche Überlegenheit. Durch die Thorakoskopie wird die Brustwandintegrität und somit die Atemmuskulatur weniger verletzt.…”
Section: Prä- Peri- Und Postoperative Optimierungsmöglichkeitenunclassified